Lemmus trimucronatus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
33. Nearctic Brown Lemming Lemmus trimucronatus French: Lemming brun / German: Brauner Lemming / Spanish: Lemming neartico Other common names: Brown Lemming Taxonomy. Arvicola trimucronata [sic] J. Richardson, 1825, Point Lake, District of Mackenzie, Canada. In the past, L. trimucronatus was synonymized with L. sibiricus. Ten subspecies recognized, but the subspecies chrysogaster may be synonymous with alascensis. Subspecies and Distribution. L.t.trimucronatusJ.Richardson,1825—NYukon,NorthwestTerritories,Nunavut,includingPrinceofWales,Somerset,KingWilliam,Baffin,andSouthamptonIs,andNManitoba(Canada). L.t.alascensisMerriam,1900—NcoastalAlaska. L.t.chrysogasterJ.A.Allen,1903—NWRussianFarEastEtoChukchiPeninsula. L.t.harroldiSwarth,1931—NunivakI(offshoreAlaska). L.t.helvolusJ.Richardson,1828—SYukon,NBritishColumbia,andNWAlberta(Canada). L.t.minusculusOsgood,1904—SWAlaska. L.t.magripesTrue,1894—PribilofIs(offshoreAlaska). L.t.phaiocephalusManning&Macpherson,1958—BanksandVictoriaIs(CanadianArcticArchipelago). ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 294-295, DOI: 10.5281/zenodo.6707142 ...